بناء الفضاء وحضور الشخصية في رواية كاماراد "رفيق الحيف والضياع " للصديق حاج أحمد - قعر المثرد, نعيم; شريط, وحيدة; شريط, نبيلة (University of Eloued جامعة الوادي, 2024)
ركّزنا في هذه الدّارسة المباركة على بناء الفضاء وحضور الشّخصيّة عند الصّدّيق الحاج أحمد في رواية كاماراد( رفيق الحيف و الضّياع ) للكشّف عن تجلّيات بناء الفضاء و حضور الشّخصيّة بتقديم ملامحها و طبائعها أيّ أفعالها الّتي تظهر من خلال تفاعلها مع الشّخصيّات الأخرى أيّ علاقتها بها فتتغيّر هذه العلاقة بتطوّر الأحداث و بتغيّر الفضاء ولقد أعطى الرّوائي دور و وظيفة وصف الشّخصيات للبطل أثناء ظهورها في الفضاء لحظة تواجده فيه. ولقد وضعنا حوصلة هذه العمل في خاتمة تحمل في طياتها أهمّ النّتائج الّتي توصّلنا إليها. In this blessed study, we focused on the construction of space and the presence of the character according to the friend Hajj Ahmed in a novel by Camarad (The Companion of Misfortune and Lost) to reveal the manifestations of the construction of space and analyze the presence of the character by presenting his features and nature, that is, his actions that appear through his encounter with other characters, that is, his relationship with them. This relationship changes with the development of events and with the change of space, and the novelist has given the role and function of describing characters to the hero as they appear in space at the moment he is in it. We have put the result of this work in a conclusion that contains the most important results we have reached.
أدب حديث ومعاصر